PERAN APARAT KELURAHAN DALAM PEMBERDAYAAN MASYARAKAT KELURAHAN TALANG SEMUT KOTA PALEMBANG - Anggleni, Andela (Magister Administrasi Publik FISIP Universitas Mulawarman, 2024)
There are officials who are lazy because of the lack of awareness of Talang Semut Village officials in community empowerment. There is a significant gap between expectations and reality in the involvement and support of Villages officials. This study aims to analyze the role of the Talang Semut Village apparatus in the implementation of community empowerment in Kedaung Village. This research uses a descriptive method with a qualitative approach. Data collection techniques used in research are observation, interviews and documentation. This study was analyzed using Soekanto's role theory (2012: 213), namely roles include norms associated with a person's position or place in society; behavior carried out by individuals in society as an organization; and individual behavior that is important to the social structure of society. The results of the study found that the Talang Semut Village apparatus played a role in community empowerment, seen from the three indicators, namely the norms of the Talang Semut Village apparatus which became the basis for community empowerment, namely openness and transparency, justice and equality, active community participation, sustainability and responsibility, collaboration and partnership and responsive to community needs. These norms have been successfully implemented and used as a benchmark in implementing the role of apparatus in community empowerment. The behavior of Talang Semut Villages officials has been successful in empowering the community, although it is considered weak because no data has been found to support arguments. However, efforts to increase community participation, identification of problems and needs, program planning, program implementation, as well as evaluation and monitoring carried out by village officials have had a positive impact and empowered the community effectively. The important behavior of individuals in the social structure of society has been successful which is reflected in the positive impact felt by the community. Communities experience increased access to public services, improved quality of life, increased participation in decision-making, and increased involvement in social and economic activities.